Spirit run : a 6,000-mile marathon through North America's stolen land - Álvarez, Noé (Catapult, 2020)
"Growing up in Yakima, Washington, Noé Álvarez worked at an apple-packing plant alongside his mother, who “slouched over a conveyor belt of fruit, shoulder to shoulder with mothers conditioned to believe this was all they could do with their lives.” A university scholarship offered escape, but as a first-generation Latino college-goer, Álvarez struggled to fit in. At nineteen, he learned about a Native American/First Nations movement called the Peace and Dignity Journeys, epic marathons meant to renew cultural connections across North America. He dropped out of school and joined a group of Dené, Secwépemc, Gitxsan, Dakelh, Apache, Tohono Oodham, Seri, Purépecha, and Maya runners, all fleeing difficult beginnings. Telling their stories alongside his own, Álvarez writes about a four-month-long journey from Canada to Guatemala that pushed him to his limits. He writes not only of overcoming hunger, thirst, and fear, dangers included stone-throwing motorists and a mountain lion, but also of asserting Indigenous and working-class humanity in a capitalist society where oil extraction, deforestation, and substance abuse wreck communities. Running through mountains, deserts, and cities, and through the Mexican territory his parents left behind, Álvarez forges a new relationship with the land, and with the act of running, carrying with him the knowledge of his parents migration, and, against all odds in a society that exploits his body and rejects his spirit, the dream of a liberated future."--Amazon.com.